The behavioural ecology of hominin locomotion: what can we learn from landscapes of fear and primate terrestriality? - Hammond, Philippa; Bobe, René; Carvalho, Susana (Frontiers in Ecology and Evolution, 2025)
A defining feature of the hominin clade is bipedality, often parcelled together with terrestriality. However, there is increasing evidence of locomotor diversity, both within the hominin clade and amongst the Miocene apes that came before them. There is also growing recognition that bipedalism might have arboreal origins and that arboreality persisted in several hominin taxa, including our own genus Homo. Furthermore, the difference between terms like “habitual” and “obligate” bipedality is not clearly defined and is often inferred from fossil features, rather than a description of each behaviour in vivo. Combining fossil and palaeoecological evidence with insights from behavioural ecology facilitates new interpretations of evolutionary pathways and highlights the importance of considering convergent evolution in the emergence of locomotor traits and characteristics. Taking such an approach also moves away from assumptions of a straight-line trajectory towards modern human locomotion and explores the likelihood that independent forms of bipedality and terrestriality arose at different times and in different combinations with other features of ape morphology and behaviour. Evidence from extant primate species can broaden our understanding of the correlates, causes, and consequences of terrestriality and can be used to generate hypotheses which are then explored further using paleontological methods. In this paper, we explore the evolutionary origins of hominin locomotion, but extend our review to include broader timescales, a wider range of primate taxa, and an integrated set of methods and disciplines for generating and testing hypotheses about locomotion. Perceived risk (or, the “landscape of fear”) is a key pressure that has selected for primate arboreality – particularly nocturnal arboreality. We propose that shifts in Plio-Pleistocene landscapes of fear – caused by declining carnivoran abundance and diversity – might also have been a key selection pressure in changes to primate locomotion, particularly papionin and hominid terrestriality. We discuss this hypothesis and propose future research avenues to explore it further. Not only will such research provide a more nuanced view of the causes and consequences of a rare behavioural trait in primates, but it could ultimately help us explain how one group of African apes came to spend all their time on the ground, and how that made them human.